2018
DOI: 10.1103/physrevlett.121.120402
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Anomaly and 2D-3D Crossover in Strongly Interacting Fermi Gases

Abstract: We present an experimental investigation of collective oscillations in harmonically trapped Fermi gases through the crossover from two to three dimensions. Specifically, we measure the frequency of the radial monopole or breathing mode as a function of dimensionality in Fermi gases with tunable interactions. The frequency of this mode is set by the adiabatic compressibility and probes the thermodynamic equation of state. In 2D, a dynamical scaling symmetry for atoms interacting via a δ-potential predicts the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 57 publications
7
68
0
Order By: Relevance
“…Many results in the many-body limit can be successfully deduced from few-body studies [20][21][22][23]. In this work, we find that our few-body results reveal two important features observed in the experiments in the presence of a nonzero effective range [10,11]: the maximum quantum anomaly reduces gradually with increasing effective range while the peak position shifts to the weakly-interacting regime. Finally, it is worth emphasizing that the fewfermion system under consideration can nowadays be routinely prepared by using microtraps [24] or optical tweezer [25,26].…”
supporting
confidence: 59%
“…Many results in the many-body limit can be successfully deduced from few-body studies [20][21][22][23]. In this work, we find that our few-body results reveal two important features observed in the experiments in the presence of a nonzero effective range [10,11]: the maximum quantum anomaly reduces gradually with increasing effective range while the peak position shifts to the weakly-interacting regime. Finally, it is worth emphasizing that the fewfermion system under consideration can nowadays be routinely prepared by using microtraps [24] or optical tweezer [25,26].…”
supporting
confidence: 59%
“…At this point, it is interesting to compare the frequency shift exhibited by a resonantly interacting p-wave Fermi superfluid and by a strongly interacting s-wave Fermi superfluid, both in two dimensions. In the latter case, the theoretically predicted maximum quantum anomaly of 10% is yet to be experimentally confirmed [62,64,65]. The main obstacle comes from the confinement-induced effective range R s , which is significant under the current experimental condition.…”
Section: B Frequency Shiftmentioning
confidence: 99%
“…Therefore, the breathing mode frequency deviates from the classically invariant value of ω c , i.e., δω B = ω B − ω c = 0. This frequency shift is now referred to as quantum anomaly [59][60][61][62][63][64][65][66]. In our case of a resonantly interacting p-wave interaction, where the 2D scattering area disappears, we anticipate that the system may also have scale-invariant zero-energy wave-functions if there is no length scale set by interactions, and in the presence of isotropic harmonic trap it has the scale-invariant breathing mode frequency ω c .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the strongly correlated regime it turns out that, the theoretical EoS determined by accurate auxiliary-field quantum Monte Carlo (AFQMC) simulations [31] slightly over-estimates the thermodynamics compared to the measured EoS [2,17,21], suggesting the inefficiency of the single-channel model. The necessity of using a more appropriate theoretical model was highlighted by the most recent measurements on the breathing mode [34][35][36], which present an interesting example of a quantum anomaly (i.e., violation of the classical scale invariance [6]). It was found that the measured breathing mode is notably lower than the prediction from the single-channel model [8,9].…”
Section: Introductionmentioning
confidence: 99%